HR from the heart : inspiring stories and strategies for building the people side of great business - Sartain, Libby, 1954- (AMACOM, 2003)
Libby Sartain talks to us with with great examples, and tough love."--Beverly Kaye, author, "Love Em or Leave Em" and "Up Is Not the Only Way."